Priming of mesenchymal stem cells with a hydrosoluble form of curcumin allows keeping their mesenchymal properties for cell‐based therapy development. Issue 10 (26th March 2021) - Colin, Margaux; Dechêne, Lola; Ceusters, Justine; Niesten, Ariane; Demazy, Catherine; Lagneaux, Laurence; Zouaoui Boudjeltia, Karim; Franck, Thierry; Van Antwerpen, Pierre; Renard, Patricia; Mathieu, Véronique; Serteyn, Didier
Abstract: Mesenchymal stem cells are increasingly studied for their use as drug‐carrier in addition to their intrinsic potential for regenerative medicine. They could be used to transport molecules with a poor bioavailability such as curcumin in order to improve their clinical usage. This natural polyphenol, well‐known for its antioxidant and anti‐inflammatory properties, has a poor solubility that limits its clinical potential. For this purpose, the use of NDS27, a curcumin salt complexed with hydroxypropyl‐beta‐cyclodextrin (HPβCD), displaying an increased solubility in aqueous solution, is preferred. This study aims to evaluate the uptake of NDS27 into skeletal muscle‐derived mesenchymal stem cells (mdMSCs) and the effects of such uptake onto their mesenchymal properties. It appeared that the uptake of NDS27 into mdMSCs is concentration‐dependent and not time‐dependent. The use of a concentration of 7 µmol/L which does not affect the viability and proliferation also allows preservation of their adhesion, invasion and T cell immunomodulatory abilities.